Reduction of Seborrhoeic Dermatitis Area Severity Index in Infantile Seborrheic Dermatitis with Malnutrition: A Case-Based Observation - Ade Gustina Siahaan; Nova Zairina Lubis (GLOBAL HEALTH SCIENCE GROUP, 2025)
Infantile seborrheic dermatitis is a common chronic inflammatory skin disorder that causes erythema and scaling on the scalp, face, and skin folds. Malnutrition in newborns can affect skin integrity and immunological responses, worsening seborrheic dermatitis symptoms. The Seborrhoeic Dermatitis Area Severity Index (SDASI) evaluates disease severity based on the size and intensity of lesions. This case report aims to describes infantile seborrheic dermatitis in a malnourished newborn who improved significantly clinically after topical medication, as measured by the SDASI. A one-month-old boy child presented with thick, yellowish scales and erythema on the head and right temporo-occipital area that had appeared one week before hospital admission.The patient was diagnosed with infantile seborrheic dermatitis and severe malnutrition (weight-for-age z-score < -3 SD per WHO growth criteria). The first SDASI score was 4. The pediatric department provided nutritional rehabilitation, while the dermatology department provided a topical corticosteroid (desoximetasone 0.25%) and emollients. During the second week of clinical exams, the SDASI score dropped to 0.2. This example demonstrates that combining nutritional support with topical therapy can lead to significant clinical improvement in infantile seborrheic dermatitis, as seen by a significant drop in SDASI score. SDASI is a valuable objective metric for monitoring sickness progression and therapy response in comparable scenarios.